Siga o fio: as possibilidades da narrativa jornalística a partir da thread no Twitter - Rocha, Bernardo Abbad da (2022)
The present work analyzes journalistic narratives in a specific social media: Twitter. It is observed that the thread (or sequence of tweets) - a native resource of the aforementioned social media - has been used, including by reference media vehicles, as a possibility of creating and/or circulating journalistic narratives in this digital space. The main objective of the research is to identify how Twitter threads are used for the production and circulation of journalistic narratives. As specific objectives, we can list: understand possible transformations of journalistic narrative on Twitter, observe in what ways the thread structure is appropriated by journalism; and understand the use of threads on Twitter by the newspaper Folha de S. Paulo. The theoreticalmethodological movement works a narrative reading of the use of the resource in question by the newspaper Folha de S. Paulo, through the analysis of sequences of tweets published in the so-called "thread of all threads", fed by the vehicle in its profile on Twitter. Therefore, the methodological approach is based, at first, on Content Analysis techniques, as proposed by Laurence Bardin (2016), in order to organize and categorize the selection of a corpus of 85 threads. In a second moment, Luiz Gonzaga Motta's Critical Analysis of Narrative (2013) is also used, analyzing the material mainly in terms of narrative expression, one of the analytical instances proposed by the author. An interview was also carried out with Mateus Camillo, Editor of Interaction and Social Networks at Folha, allowing the comparison of some questions raised by the previous movements of the analysis. Among the results worked from the study, it is highlighted that the newspaper Folha de S. Paulo uses Twitter threads in different ways, aiming at the creation and circulation of its own journalistic narratives. The analysis of a corpus of 85 narrative sequences produced by Folha de S. Paulo on its Twitter profile showed that they are used by the newspaper in order to attract readers and also produce and circulate content that in other media, such as the printed newspaper. and the website itself, would not be possible. From an extensive analysis, with the observation and categorization of the corpus, different uses of threads to create and/or circulate journalistic narratives were observed, which were grouped into seven categories. Whether to chronologically reorganize certain facts or to delve into a certain topic, we sought to identify and discuss these various narrative uses of Twitter threads by journalism.